Situation Report: Hungary, 7 October 1966 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Rusk Meets with Hungarian Foreign Minister Hungarian Autumn Maneuvers Meeting of Trade Union Council State Procurement of Bread and Fodder Grain New Power Plant under Construction